THE INFLUENCE OF PERCEIVED INFORMATION TECHNOLOGY, PERCEIVED EASE OF USE, PERCEIVED RISK AND SERVICE FEATURES ON USING BCA INTERNET BANKING - Pangemanan, Ivan (Universitas Sam Ratulangi, 2013)
Internet banking usage rate increased with availability features that support users for their daily activities or a part of the lifestyle. With the Internet Banking we can conduct transactions anywhere, with anyone. Today, many banks are promoting internet banking as one of their flagship programs. Because customers do not need to go to the bank in the transaction. BCA internet banking as one of the leading banks in Indonesia has been developing ways to attract the attention of customers, one of them by providing internet banking. Many people still wonder whether the technology used is quite good, is easy to use, there are risks that can occur with the use of internet banking, and the features contained in the Internet banking can satisfy customers. This study is to analyze The influence of Perceived Information Technology, Perceived Ease of Use, Perceived Risk and Service Features on using BCA Internet Banking uses quantitative method. The sample of respondents are 100 peoples who are customers of the BCA Bank. The result shows the Perceived Information technology, Perceived Ease of Use, Perceived Risk and Service Features have a significant impact to using BCA Internet Banking. The recommendation for company are continues to strive to maintain and improve the perception of information technology in direct contact with consumers, also to bring awareness to customers that use internet banking also has the risk of resulting in an understanding of the risk on customers using internet banking, therefore the company continues to actively promote both the internet banking facility with brochures and direct mail to customers and the company still update the features required by the customer. Keywords: perceived information technology, ease of use, risk, services features